Malaysian multimedia content industry - Badi, Maimona J.; Zeki, Akram M. (IIUM Press, 2015)
Generally, this chapter discusses issues and challenges of multimedia content industry in Malaysia. Specifically, the chapter provides an overview of the latest multimedia contents, how to implement them in the industry and some examples of industries that has multimedia content in it. This includes education, medical, commercial, entertainment and communication industries. The chapter divided into the following sections: introduction which gives general overview of the multimedia content industry, the technological trend towards multimedia, considerable tools for adopting multimedia, development of multimedia content software, model of applying multimedia content across the industries, differences between multimedia contents and digital content industry and multimedia content industry in Malaysia.